2019
DOI: 10.3748/wjg.v25.i47.6866
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of inflammatory bowel disease in South America: A systematic review

Abstract: BACKGROUNDThe worldwide epidemiology of inflammatory bowel disease (IBD) is rapidly changing. Increasing Crohn’s disease (CD) and ulcerative colitis (UC) incidence and prevalence have been recorded in developing regions such as Asia, Africa and Eastern Europe where it was previously thought to be uncommon. Whether this is also the case in South America is not well known. Demonstration that developing regions worldwide have increasing IBD incidence would indicate that environmental change plays a significant ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 28 publications
(67 reference statements)
4
32
0
7
Order By: Relevance
“…In summary, consistent with other recent epidemiological reviews of IBD in Latin America, 5,6,8 we noted an increase in the incidence and prevalence of UC in this population. Furthermore, despite a considerable proportion of patients with UC in Latin America having moderate to severe disease and requiring surgery, advanced therapies for the treatment of UC were underutilised.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In summary, consistent with other recent epidemiological reviews of IBD in Latin America, 5,6,8 we noted an increase in the incidence and prevalence of UC in this population. Furthermore, despite a considerable proportion of patients with UC in Latin America having moderate to severe disease and requiring surgery, advanced therapies for the treatment of UC were underutilised.…”
Section: Resultssupporting
confidence: 92%
“…The public health system in Latin America faces a number of challenges, and health outcomes need to be improved by addressing the gaps in public health capacity. 49 In agreement with previous review articles, 6 8 additional high-quality standardised epidemiological studies are required to provide a clearer picture of the burden of UC in Latin America. This review may act as a starting point to better study UC epidemiology in a region that provides many opportunities for further local research.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…[ 8 ] The prevalence of UC in urban population is relatively high. [ 9 ] So far, the pathogenesis of UC is not very clear, but it has been confirmed that genes, environment, intestinal microorganisms, and autoimmune factors are involved in the pathogenesis process of UC. [ 1 , 10 , 11 ] A prospective study [ 12 ] found that dietary factors are closely related to the onset of UC, and meat in the diet (especially red meat and processed meat, alcoholic beverages, and protein intake) is also associated with an increased likelihood of recurrence in UC patients.…”
Section: Introductionmentioning
confidence: 99%